5- Shopping for Health: Affliction and Response in a South African Village - Mutebi, Frederick Golooba; Tollman, Stephen M. (African Sociological Review, 2023)
Much research on health-seeking behaviour focuses on the influence of folk beliefs. The role of traditional practitioners and healing practices feature prominently. On the other hand, in thinking about service delivery in the health sector, policy experts working for governments and the development fraternity focus on physical infrastructure, supplies, equipment, and resources, human and financial, as the critical elements in ensuring quality provision by providers and consistent use by consumers. Folk beliefs about illness causation and treatment and how they may or may not influence service use do not feature in policy discussions. Nor are they a major feature of medical curricula. This paper shows, as does other evidence, that this approach to health education and policy making is inadequate. It addresses three questions. How do the people of Tiko respond to ill-health? What influences their health-seeking behaviour? What do their responses imply for public policy generally and health policy and practice in particular? It shows that, as elsewhere, response to ill-health is pragmatic and pluralistic. Folk beliefs are important in decision making. So are other factors, including experiences with the formal health system and access to social and financial resources. It shows that the search for therapy is not a powerless and blind search, but one based on rational decision-making, in which many actors participate. It adds to the evidence that building functioning health systems and delivering services that address users’ needs demands more than technocratic fixes.